The Very Model of a Modern Engineer: Status, Education, and the Engineering Institute of Canada, 1925-1932 - Martin-Nielsen, Janet (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2007)
AbstractBetween 1925 and 1932, the Engineering Institute of Canada (EIC)—one of the oldest professional organizations for engineers in Canada—advocated vigorously for the inclusion of cultural and communications courses in university engineering curricula. Motivated by the perceived inferiority of engineering in comparison to the medical and law professions, this effort led to an important reconsideration of the social status and professional identity of engineers. The EIC challenged the self-identification of engineers as technical experts and forced the engineering profession to re-evaluate its pedagogical and public priorities. This paper documents changes in engineering mentalities between 1925 and 1932 and argues that, in these years, Canadian engineers fostered a broader understanding of their role in society.